Contextual Factors Affecting Continuity of Follow-Up Care After Hospital Discharge for Patients with Chronic Diseases in Sudan: A Qualitative Study with Causal Loop Diagram Insights - Asma MohamedSharif; Armin Gemperli (Health Services Insights)
This study aims to identify factors influencing the continuity of follow-up care after hospital discharge from the perspectives of physicians and key healthcare stakeholders and map their interactions to facilitate understanding of dynamic relationships. We conducted audio-recorded semi-structured interviews with 17 participants (10 medical doctors, 3 state key informants, and 4 federal key informants) in Khartoum State, Sudan. Data analysis included thematic analysis to identify the factors and purposive text analysis to develop a causal loop diagram. We identified 39 factors affecting the continuity of follow-up care from hospital to home, categorized into 5 challenges: follow-up care adherence, quality of pre-discharge patient education, efficiency of the referral system, primary healthcare center accessibility, and quality improvement efforts. The study identified 2 balancing loops and 5 reinforcement feedback loops affecting follow-up care post-hospital discharge. The low adherence to follow-up care proposes quality improvement efforts as a solution, however, the high workload, resource depletion, referral system inefficiency, and quality improvement stagnation reinforcing loops impede progress in this direction. We recommend enhancing pre-discharge patient education and using multisectoral approaches to improve primary healthcare, optimize referrals with digital tools, and address staff turnover, to strengthen follow-up care.